Impact of Stacking Faults and Domain Boundaries on the Electronic Transport in Cubic Silicon Carbide Probed by Conductive Atomic Force Microscopy. (15th January 2020) - Giannazzo, Filippo; Greco, Giuseppe; Di Franco, Salvatore; Fiorenza, Patrick; Deretzis, Ioannis; La Magna, Antonino; Bongiorno, Corrado; Zimbone, Massimo; La Via, Francesco; Zielinski, Marcin; Roccaforte, Fabrizio
Abstract: In spite of its great promise for energy‐efficient power conversion, the electronic quality of cubic silicon carbide (3C‐SiC) on silicon is currently limited by the presence of a variety of extended defects in the heteroepitaxial material. However, the specific role of the different defects on the electronic transport is still under debate. A macro‐ and nanoscale characterization of Schottky contacts on 3C‐SiC/Si is carried out to elucidate the impact of the anti‐phase boundaries (APBs) and stacking faults (SFs) on the forward and reverse current–voltage characteristics of these devices. Current mapping of 3C‐SiC by conductive atomic force microscopy directly shows the role of APBs as the main defects responsible of the reverse bias leakage, while both APBs and SFs are shown to work as preferential current paths under forward polarization. Distinct differences between these two types of defects are also confirmed by electronic transport simulations of a front‐to‐back contacted SF and APB. These experimental and simulation results provide a picture of the role played by different types of extended defects on the electrical transport in vertical or quasi‐vertical devices based on 3C‐SiC/Si, and can serve as a guide for improving material quality by defects engineering. Abstract : Current mapping by conductive atomic force microscopy is employed to investigate the electrical properties of extended defects in cubic silicon carbide (3C‐SiC) on silicon; that is, anti‐phase boundaries (APBs) and stacking faults (SFs). APBs are responsible of the leakage current under reverse bias polarization of the Pt/3C‐SiC Schottky junction, whereas both APBs and SFs contribute to conduction under forward polarization.